Development of Motion System Animation Videos (SkelToon) to Increase Learning Motivation - Widianingsih, Mia; Miarsyah, Mieke; Ristanto, Rizhal Hendi (FMIPA UNNES, 2021)
The purpose of this study was to analyze how the use of SkelToon animated video learning media in improving students' learning motivation on motion system materials. This research was conducted at SMAN 30 Kab. Tangerang. The method used in this research is a 4D research and development model method consisting of four stages, namely the definition, design, development, and distribution of research design one group pretest-posttest design. The subjects in this study were 21 students who sat in grade XI mipa. The research instrument used in this research is a non-test instrument in the form of a learning motivation questionnaire. The results of media feasibility test by validator showed that animated video media designed in the category is very valid, and in this study statistical test using t-test of paired samples that showed that the significance value obtained in this study was 0.000 which is less than 0.05 , then based on the anal results.